2012
DOI: 10.1021/ie301569q
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Cinnamaldehyde over Pt and Pd Supported on Multiwalled Carbon Nanotubes in a CO2-Expanded Alcoholic Medium

Abstract: Pt/MWCNT and Pd/MWCNT nanocatalysts were prepared via a liquid reduction method. The selective hydrogenation of cinnamaldehyde (CAL) was investigated over 5.0 wt.% Pt/MWCNT and 5.0 wt.% Pd/MWCNT catalysts in a CO 2 -expanded alcoholic medium at different reaction conditions. The hydrogenation selectivities over these two catalyst types were shown to be entirely different. It was found that the Pt/MWCNT catalysts are highly selective for CO bonds, giving the unsaturated alcohol a selectivity for cinnamyl alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 27 publications
1
19
0
2
Order By: Relevance
“…Cinnamaldehyde (CAL) is a particularly important a,bunsaturated aldehyde, since its partial hydrogenation products are important intermediates in the manufacture of chemicals (particularly perfumes, flavors, and pharmaceuticals) [2,3]. Also, it is considered a good model for investigating the catalytic behavior of the microstructures of heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamaldehyde (CAL) is a particularly important a,bunsaturated aldehyde, since its partial hydrogenation products are important intermediates in the manufacture of chemicals (particularly perfumes, flavors, and pharmaceuticals) [2,3]. Also, it is considered a good model for investigating the catalytic behavior of the microstructures of heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Pd is well known to be active for C=C hydrogenation but inert for C=O hydrogenation, thus it is usually employed as a main active metal for the hydrogenation of CAL to HALD . To further improve the performance of Pd‐based catalysts, different additives are usually applied.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Table S2 summarizes the selective hydrogenation of CAL over the Pd-based catalysts reported from the literature. The 5.0 wt %Pd/MWCNT catalyst designed by Zhao et al gave 91.3% HALD selectivity at 98.6% CAL conversion under 40 bar H 2 pressure and 148 bar CO 2 pressure [59]. Chen et al reported 80% HALD selectivity with 100% CAL conversion over 3.0 wt % Pd/(SH)MSC catalyst [3].…”
Section: Hydrogenation Of Cal To Hald Over Pd-ni/sba-15mentioning
confidence: 99%